KERAGAAN AGRIBISNIS KOPI DI KABUPATEN WONOGIRI - Hasan, Fuad; Murniyanto, Eko; Siti Rahayu, Endang (Inisiasi, 2024)
This study aims to analyze the performance of coffee agribusiness in Wonogiri regency which is seen from the availability of inputs, cultivation techniques, post-harvest handling, economics and marketing, and the role of supporting institutions. Primary data were collected using interview techniques with key informants consisting of farmers, managers of farmer groups and farmer group associations, MSMEs, traders, and agricultural extension officers. Data were analyzed using descriptive techniques. The results of the analysis showed that there were no quality seeds available and limited fertilizer availability; many farmers' cultivation techniques were still not in accordance with the coffee GAP; many farmers still did not consider the quality of the harvest; coffee contributed to the income of farmer households where profits would be obtained in the 4th year after planting; there were three levels of coffee marketing channels with intermediary institutions, namely farmer groups/farmer groups, MSMEs, collectors, shops/cafes, wholesalers, and factories. Agribusiness support institutions in Wonogiri include farmer groups, local governments, CSR, and coffee communities.